Cement Stabilization/Solidification of Heavy Metal-Contaminated Sediments Aided by Coal Fly Ash - Cheng Zhu; Xiaolei Jia; Panyue Zhang; Junpei Ye; Hongjie Wang (The Global Environmental Engineers, 2017)
Discharge of various wastewater containing heavy metals from metallurgical, chemical engineering industries, etc. into water body results in the accumulation of heavy metals in sediments of rivers and lakes, and further severe sediment contamination. When the severely contaminated sediments are dredged, they must be handled before disposal. In this paper, the dredged sediments were stabilized/solidified with cement aided by coal fly ash. The compressive strength of stabilization/solidification specimens decreased with the increase of sediment/binder ratio. All specimens showed a satisfactory compressive strength except that the compressive strength of the specimen with the high sediment/binder ration of 3.33 was lower than 0.35 MPa, the requirement of US EPA. Coal fly ash effectively acted as the binder, but the excessive addition of coal fly ash resulted in the reduction of specimen compressive strength. The pH of TCLP leachates for the specimens, which met the requirement of the compressive strength, was distributed between 11.07 and 12.50, and the heavy metal concentration of the TCLP leachates was lower than 0.029 mg/L. A similar trend of acid neutralization capacity of the stabilization/solidification specimens was observed as that of the compressive strength. Curing in a hermetically sealed plastic bag at ambient temperature and a longer curing period improved the stabilization/solidification effect. Humidity and temperature played an important role during curing period. Under an aggressive condition with a fixed leachate pH of 4, the stabilization/solidification technology increased the heavy metals fixed to 88.47%, 93.30% and 87.71% for zinc, lead and cadmium, respectively, and the concentration of zinc, lead and cadmium in the leachates was lower than the limits of the identification standards for hazardous wastes-identification for extraction toxicity (GB 5085.3-2007). So cement stabilization/solidification aided by coal fly ash can be an alternative disposal technology for dredged sediments contaminated by heavy metals.